Risky sexual behavior and self-rated mental health among young adults in Skåne, Sweden - a cross-sectional study - Anna Karle; Anette Agardh; Markus Larsson; Malachi Ochieng Arunda (BMC, 2023)
Abstract Background Risky sexual behavior is a public health challenge that significantly affects young people's health and well-being in Sweden and throughout the world. Moreover, poor mental health, anxiety and depression among adolescents and young adults have increased in recent years. However, although hypothesized, the associations between general mental health and risky sexual behavior among young adults are less established. Thus, this study aimed to examine the association between self-rated mental health and risky sexual behavior among young adults in southern Sweden. Methods Population-based, cross-sectional survey data from 2968 participants aged 18-30 years old residing in southern Sweden was used (response rate 42%). The survey included questions on sexual behavior, alcohol habits, sociodemographic background, and mental health. Logistic regression was used to examine the associations between mental health, depression, anxiety, and risky sexual behavior, stratified by sex (gender). Indicators for risky sexual behavior included not using a condom, non-condom use with casual partner, and multiple (≥2) sexual partners during the last year. Results Generally, male participants rated their depression and anxiety levels considerably lower than their female counterparts. Poor mental health, high depression, and high anxiety scores (levels) were significantly associated with having multiple sexual partners among among female participants; adjusted odds ratios (aOR) was 1.3 (95% CI 1.01 to 1.71). However, findings among males were not statistically significant. Furthermore, overall results indicated that higher depression and anxiety scores were associated with 1.4 and 1.6 higher odds, respectively, of not using condom with a casual partner in the most recent sexual encounter. Similarly, higher anxiety scores were associated with non-condom use in the latest sexual encounter, aOR 1.4 (1.1-1.7), but no significant gender-specific associations were found. Conclusion The associations found between poor mental health factors and multiple sex partners among females warrant consideration in future public health interventions. Further research to increase the understanding of the causal mechanisms that link mental health factors and risky sexual behavior, especially multiple sex partners, among young adult females is needed to support evidence-based interventions.